A narrative review of medicinal uses and ethnopharmacological properties of wild yam (Dioscorea sylvatica Eckl). - Alfred Maroyi (Student's Journal of Health Research Africa, 2026)
Dioscorea sylvatica Eckl. is a climber or vine with a large underground fleshy tuber widely used in traditional medicine in Southern Africa. This narrative review is aimed at synthesizing traditional ecological knowledge about the medicinal uses and ethnopharmacological properties of D. sylvatica. A systematic review of scientific literature on the therapeutic potential and ethnopharmacological properties of D. sylvatica was conducted following the Preferred Reporting Items for Systematic Reviews and meta-analyses (PRISMA). The literature search was conducted using databases PubMed, Web of Science, ScienceDirect, Google Scholar, SpringerLink, Scopus and SciELO, as well as pre-electronic literature sources such as book chapters, books and other scientific publications obtained from the university library. The crude extracts of D. sylvatica are used as a blood purifier, charm, ritual and ethnoveterinary medicine, and traditional medicine against circulation problems, gonorrhoea, inflammation, respiratory infections, rheumatism, skin problems, cuts, sores and wounds. The species is characterized by 2-carboxyarabinitol, alkaloids, anthocyanins, bibenzyl, calcium oxalate crystals, diarylnonanoids, flavonoids, glycosides, pyrogallol, sapogenin, saponins, shikimic acid, tannins and terpenoids. The crude extracts of D. sylvatica and phytochemical compounds isolated from the species demonstrated anti-acetylcholinesterase, antibacterial, antifungal, antimycobacterial, anti-inflammatory, antioxidant, antibiotic-potentiating and cytotoxicity activities. Future studies should focus on detailed ethnopharmacological evaluation of D. sylvatica, particularly its phytochemistry, biological activities and toxicological assessments, in vivo, pre-clinical and clinical studies.